EFEK TINGGI MUKA AIR TANAH DAN PEMUPUKAN TERHADAP EMISI CO2 PADA TANAH GAMBUT DENGAN SERASAH DAUN AKASIA (Acacia crassicarpa) - Sianturi, Merry; ', Wawan; ', Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Indonesia has the largest peatland among the tropical countries which are spread in Sumatra mainly in province of Riau, Kalimantan and Papua. This study aims to know the effect of water level and fertilization N, P, K on CO2 emissions in peatland with litter of akasia (Acacia crassicarpa). This research was conducted in the Screen House, Plant Laboratory Faculty of Agriculture, University of Riau, from July to December 2013. This research was conducted experimentally using completely randomized design (CRD) of non-factorial with 6 treatments and 3 replications. The data obtained were analyzed descriptively and then the data is presented in tabular form. Parameters observed were CO2 emissions. The results showed that the increase of water level depth from 30 cm to 90 cm without fertilizer and with fertilizer N, P, K increase CO2 emissions were observed in October. However, in November and December observation, CO2 emissions were obtained in each treatment is inconsistent comparing in Oktober observation. Treatment of water level with fertilizer N, P, K result in CO2 emissions lower than treatment without fertilizer. Key words: water level, fertilization and CO2 emissions